Population genetic structure and performing assignment test on six Iranian native goats using simple sequence repeat markers - Bizhan MAHMOUDI; Jamal FAYAZI; Reza SHOKRI-GHARELO; Ghader MANAFIAZAR (Journal of Central European Agriculture, 2019)
The native goat breeds could be better managed and their genetic diversity to be conserved through identification of population genetic structure. Total of 299 animals from six goat breeds, which are major native breeds of Iran, were used to study their genetic structure and understand relationship among the breeds using SSR markers on 13 microsatellite loci. The breeds were selected from different geographic regions of Iran. The results indicated that there is high genetic diversity at the population level (HS of 0.78) and at the species level (HT of 0.86). The level of inbreeding was low across the breeds and even genetic diversion was observed among them, indicating a low level of gene flow at the regional scale. Some level of admixtures was observed among breeds, which supported by clustering of the breeds based on their geographic origin. Analysis of the population genetic structure indicated that all breeds are grouped into four clusters. The assignment accuracy per locus ranged from 40.1% (BM4621) to 66.9% (oarJMP23). The assignment power of microsatellites based on the Bayesian method had positive correlation with the number of alleles and gene differentiation coefficient (Gst) per locus. In conclusion, this study provided a genetic profile for the conservation and improvement and origin of the studied breeds.